2005
DOI: 10.1128/aem.71.4.2046-2052.2005
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Polyhydroxyalkanoate from Styrene and Phenylacetic Acid by Pseudomonas putida CA-3

Abstract: Pseudomonas putida CA-3 is capable of converting the aromatic hydrocarbon styrene, its metabolite phenylacetic acid, and glucose into polyhydroxyalkanoate (PHA) when a limiting concentration of nitrogen (as sodium ammonium phosphate) is supplied to the growth medium. PHA accumulation occurs to a low level when the nitrogen concentration drops below 26.8 mg/liter and increases rapidly once the nitrogen is no longer detectable in the growth medium. The depletion of nitrogen and the onset of PHA accumulation coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 33 publications
6
95
2
1
Order By: Relevance
“…Previous studies have reported the accumulation of polyP by Escherichia coli in response to nitrogen limitation (3,11). As previously reported, negligible levels (0.3% CDW) of mclPHA were observed in P. putida CA-3 cells 5 h after inoculation (31) (Fig. 2).…”
supporting
confidence: 66%
“…Previous studies have reported the accumulation of polyP by Escherichia coli in response to nitrogen limitation (3,11). As previously reported, negligible levels (0.3% CDW) of mclPHA were observed in P. putida CA-3 cells 5 h after inoculation (31) (Fig. 2).…”
supporting
confidence: 66%
“…A number of Pseudomonas strains (P. putida KT2440, CA-3 and GO16, P. chlororaphis 555) were tested for their ability to grow and produce PHA on a range of plant oils. The Pseudomonas putida strains have previously been used to produce mcl-PHA from a variety of substrates 34,35,36 . Other P. chlororaphis strains have been used to produce mcl-PHA from palm kernel oil 14 .…”
Section: Growth and Pha Production In Shaken Flasks With Plant Oilsmentioning
confidence: 99%
“…6). Samples were obtained from cultures grown under PHA accumulation conditions previously described (19,28). A protein of ϳ60 kDa in size which is present in wild-type CA-3 (Fig.…”
Section: Resultsmentioning
confidence: 99%